Inhibitory effect of cold atmospheric plasma on chronic wound-related multispecies biofilms - de Oliveira, Maria Alcionéia Carvalho [UNESP]; Lima, Gabriela de Morais Gouvêa [UNESP]; Nishime, Thalita M. Castaldelli; Gontijo, Aline Vidal Lacerda [UNESP]; de Menezes, Beatriz Rossi Canuto; Caliari, Marcelo Vidigal; Kostov, Konstantin Georgiev [UNESP]; Koga-Ito, Cristiane Yumi [UNESP] (MDPI, 2021)
The presence of microbial biofilms in the wounds affects negatively the healing process and can contribute to therapeutic failures. This study aimed to establish the effective parameters of cold atmospheric plasma (CAP) against wound-related multispecies and monospecies biofilms, and to evaluate the cytotoxicity and genotoxicity of the protocol. Monospecies and multispecies biofilms were formed by methicillin-resistant Staphylococcus aureus (MRSA), Pseudomonas aeruginosa and Enterococcus faecalis. The monospecies biofilms were grown in 96 wells plates and multispecies biofilm were formed on collagen membranes. The biofilms were exposed to helium CAP for 1, 3, 5 and 7 min. In monospecies biofilms, the inhibitory effect was detected after 1 min of exposure for E. faecalis and after 3 min for MRSA. A reduction in P. aeruginosa biofilm’s viability was detected after 7 min of exposure. For the multispecies biofilms, the reduction in the overall viability was detected after 5 min of exposure to CAP. Additionally, cytotoxicity and genotoxicity were evaluated by MTT assay and static cytometry, respectively. CAP showed low cytotoxicity and no genotoxicity to mouse fibroblastic cell line (3T3). It could be concluded that He-CAP showed inhibitory effect on wound-related multispecies biofilms, with low cytotoxicity and genotoxicity to mammalian cells. These findings point out the potential application of CAP in wound care.
Keywords: Biofilm; Plasma jet; Wounds